SPECIES COMPOSITION OF PLANT PATHOGENIC FLORA OF SOYBEAN SEEDS - Поспєлова, Г. Д. (Scientific Progress & Innovations, 2015)
The results of photoexpress of soybean seeds are presented. The quality indicators, the degree of contamination and species composition of pathogenic microorganisms are defined. The representatives of mushrooms (genus Alternaria, Fusarium, Peronos-pora, Cladosporium, Botrytis, Aspergillus, Penicil-lium, Mucor) and bacterial flora (bacteria of the genus Pseudomonas) are identified. Among the pathogenic microorganisms was widely spread fungi of the genus Alternaria (26–35 %) and Mucor (22–47 %). The species composition of pathogens is varies on different soybean varieties. It was more diverse of soybean seed’s variety Kyivs’ka 98.